The Effect of Recommended Mouthwashes on the Shear Bond Strength of Orthodontic Brackets During the Covid-19 Pandemic: An In Vitro Study - AmirHossein Mirhashemi; Rashin Bahrami (Tehran University of Medical Sciences, 2023)
Objectives: This study aimed to assess the impact of recommended mouthwashes (chlorhexidine, hydrogen peroxide, and povidone-iodine) used during the COVID-19 pandemic on the shear bond strength (SBS) of orthodontic brackets. Materials and Methods: A total of 52 human premolar teeth were divided into 4 groups (N=13) consisting of no intervention (control group), 0.2% chlorhexidine, 1.5% hydrogen peroxide, and 0.2% povidone-iodine. Following immersion in the mouthwashes, orthodontic brackets were bonded to enamel surfaces. Then, the brackets were debonded using a universal testing machine. The specimens were evaluated with a scanning electron microscope (SEM) and adhesive remnant index (ARI) score was assessed. One-way ANOVA and Tukey test were used for statistical analysis and P<0.05 was considered significant. Results: The SBS of the experimental groups decreased compared to the control group. The highest SBS mean value was observed in the controls and the lowest was found in the 0.2% povidone-iodine group. Significant differences in SBS values were found between the 0.2% povidone-iodine group and the 1.5% hydrogen peroxide group when compared to the control group (P=0.023, P=0.028, respectively). SEM analysis revealed similar characteristics among the groups, with a closer resemblance between the chlorhexidine and control groups. Additionally, these groups exhibited greater etching depth compared to the other groups. Conclusion: Our findings highlight the importance of careful selection and application of mouthwashes in orthodontic procedures. While 1.5% hydrogen peroxide and 0.2% povidone-iodine may have some impact on bond strength, their use can still be considered acceptable within defined limits.